Synthesis and characterization of new polyamides derived from alanine and valine derivatives - El-Faham, Ayman (BioMed Central, 2012)
BACKGROUND: Many efforts have been recently devoted to design, investigate and synthesize biocompatible, biodegradable polymers for applications in medicine for either the fabrication of biodegradable devices or as drug delivery systems. Many of them consist of condensation of polymers having incorporated peptide linkages susceptible to enzymatic cleavage. Polyamides (PAs) containing α-amino acid residues such as L-leucine, L-alanine and L-phenylalanine have been reported as biodegradable materials. Furthermore, polyamides (PAs) derived from C(10) and C(14) dicarboxylic acids and amide-diamines derived from 1,6-hexanediamine or 1,12-dodecanediamine and L-phenylalanine, L-valyl-L-phenylalanine or L-phenylalanyl-L-valine residues have been reported as biocompatible polymers. We have previously described the synthesis and thermal properties of a new type of polyamides-containing amino acids based on eight new symmetric meta-oriented protected diamines derived from coupling of amino acids namely; Fomc-glycine, Fmoc-alanine, Fomc-valine and Fomc-leucine with m-phenylene diamine or 2,6-diaminopyridine. Results revealed that incorporation of pyridine onto the polymeric backbone of all series decreases the thermal stability. Here we describe another family of polyamides based on benzene dicarboxylic acid, pyridine dicarboxylic acid, and α-amino acid linked to benzidine and 4,4(′)-oxydianiline to study the effect of the dicarboxylic acid as well as the amino acids on the nature and thermal stability of the polymers. RESULTS: We report here the preparation of a new type of polyamides based on benzene dicarboxylic acid, pyridine dicarboxylic acid, and α-amino acid linked to benzidine and 4,4(′)-oxydianiline to study the effect of the dicarboxylic acid as well as the amino acids on the nature and thermal stability of polymers. The thermal properties of the polymers were evaluated by different techniques. Results revealed that structure-thermal property correlation based on changing the dicarboxylic acid monomer or the diamine monomer demonstrated an interesting connection between a single change (changing the dicarboxylic acids in each series while the diamine is fixed) and thermal properties. The newly prepared polymers may possess biodegradability and thus may find some applications as novel biomaterials. CONCLUSIONS: The thermal properties of the new type of polyamides based on benzene dicarboxylic acid, pyridine dicarboxylic acid, and α-amino acid (alanine and valine) linked to benzidine and 4,4′-oxydianiline were evaluated by thermal gravimetric (TG), differential thermal gravimetric (DTG) and differential thermal analysis (DTA) techniques. Results revealed that the structure-thermal property correlation based on changing the dicarboxylic acid monomer or the diamine monomer demonstrated an interesting connection between a single change (changing the dicarboxylic acids in each series while the diamine is fixed) and thermal properties. In addition, pyridine-containing polymers exhibited semicrystalline characteristic with melting temperature, T(m). where none of the valine-containing polymers showed a melting and crystallization peak indicating that the polymers were amorphous. This is expected since L-valine side chain can inhibit close packing and eliminate crystallization. The newly prepared polymers may possess biodegradability and thus may find some applications as novel biomaterials.